Comprehensive Assessment and Standardization of Solid Phase Multiplex‐Bead Arrays for the Detection of Antibodies to HLA. Issue 7 (13th June 2013) - Reed, E. F.; Rao, P.; Zhang, Z.; Gebel, H.; Bray, R. A.; Guleria, I.; Lunz, J.; Mohanakumar, T.; Nickerson, P.; Tambur, A. R.; Zeevi, A.; Heeger, P. S.; et al.
Abstract Solid phase multiplex‐bead arrays for the detection and characterization of HLA antibodies provide increased sensitivity and specificity compared to conventional lymphocyte‐based assays. Assay variability due to inconsistencies in commercial kits and differences in standard operating procedures (SOP) hamper comparison of results between laboratories. The Clinical Trials in Organ Transplantation Antibody Core Laboratories investigated sources of assay variation and determined if reproducibility improved through utilization of SOP, common reagents and normalization algorithms. Ten commercial kits from two manufacturers were assessed in each of seven laboratories using 20 HLA reference sera. Implementation of a standardized (vs. a nonstandardized) operating procedure greatly reduced MFI variation from 62% to 25%. Although laboratory agreements exceeded 90% (R2), small systematic differences were observed suggesting center specific factors still contribute to variation. MFI varied according to manufacturer, kit, bead type and lot. ROC analyses showed excellent consistency in antibody assignments between manufacturers (AUC > 0.9) and suggested optimal cutoffs from 1000 to 1500 MFI. Global normalization further reduced MFI variation to levels near 20%. Standardization and normalization of solid phase HLA antibody tests will enable comparison of data across laboratories for clinical trials and diagnostic testing.